Sustainable Agricultural Transformation through the Rice–Duck–Turi Integrated Farming System in the Karya Makmur Farmer Group in Air Satan Village, Musi Rawas Regency - Sumini; Laksono, Judo; Bagus Dimas Setiawan; Mukhlis (Unram Journal of Community Service, 2025)
Rice farming remains a vital sector for rural communities in Indonesia, but dependence on conventional systems has resulted in low productivity and economic instability for farmers. This activity aims to introduce the Rice-Duck-Turi (RDT) system as a sustainable Integrated Farming System (IFS) model applied to the Karya Makmur Farmer Group in Air Satan Village, Musi Rawas Regency. This approach integrates rice cultivation with duck farming in the fields and the planting of turi (Sesbania spp) on the embankments. The research method used a participatory approach through socialization, training, mentoring, and field evaluation activities. The results of this activity show that the Paitri system can reduce the use of chemical fertilizers by up to 25% and provide additional income through duck egg and meat production. The integration of turi plays a role in providing natural organic fertilizer and forage, while also improving soil fertility. This system also strengthens social solidarity and economic independence among farmers through mutual assistance and collective learning. The implementation of the Paitri system has proven to be an efficient, environmentally friendly, and economically valuable sustainable agricultural innovation that can be replicated in other rural areas to strengthen local food security.